Ligand‐independent activation of MET through IGF‐1/IGF‐1R signaling. Issue 7 (17th April 2013) - Varkaris, Andreas; Gaur, Sanchaika; Parikh, Nila U.; Song, Jian H.; Dayyani, Farshid; Jin, Jung‐Kang; Logothetis, Christopher J.; Gallick, Gary E.
Abstract : The receptor tyrosine kinase, MET, has been implicated in tumorigenesis and metastasis of many solid tumors, by multiple mechanisms, including cross talk with epidermal growth factor receptor. In this study, we examined the role of insulin‐like growth factor receptor‐1 (IGF‐1R) signaling in MET activation, focusing on prostate cancer cells. Stimulation of the prostate cancer cell line PC3 with IGF‐1 induces a delayed phosphorylation of MET at multiple sites (indicative of full activation), reaching a maximum 18 hr after IGF‐1 addition. MET activation does not require the sole MET ligand hepatocyte growth factor (HGF), but does require transcription to occur. Furthermore, direct injection of IGF‐1 is sufficient to induce MET activation in vivo, in a PC3 xenograft model. Pharmacologic or genetic inhibition of the tyrosine kinase, Src, abolishes MET phosphorylation, and expression of activated Src is sufficient to induce Met phosphorylation in the absence of IGF‐1 stimulation. Activated MET is essential for IGF‐1‐mediated increased migration of PC3 cells, demonstrating an important biologic effect of IGF‐1‐mediated MET activation. Finally, we demonstrate that IGF‐1‐induced delayed MET activation occurs in multiple cell lines which express both the receptors, suggesting that IGF‐1R‐mediated MET activation may contribute to tumorigenic properties of multiple cancer types when both growth factor receptors are expressed. The results further suggest that MET may be activated by multiple receptor tyrosine kinase receptors, and dual targeting of these receptors may be important therapeutically. Abstract : What's new? MET tyrosine kinase plays an important role in the genesis of solid tumors, though the mechanism that instigates its deviant behavior, particularly with regard to hepatocyte growth factor (HGF) binding, is not fully understood. This report provides the first evidence for HGF‐independent delayed MET activation via insulin‐like growth factor receptor‐1 (IGF‐1R) signaling in prostate cancer cells. The mechanism is dependent on transcription and requires activation of the tyrosine kinase Src. The findings not only implicate IGF‐1R in MET activation but also support the idea that receptor cross‐talk in solid tumors is of therapeutic importance.